Tratamiento de miasis oral con Ivermectina notificación de tres casos causados por Cochliomyia Hominivorax (COQUEREL) - Duque-Serna, Francisco Levi; Valderrama-Hernández, Rafael; González-Robledo, Jorge Alonso (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Myiasis is the infestation of the body tissues of man and animals by the larvae of Diptera (Two winged flies). It has been observed in differents areas of humans, but is uncommon in the oral cavity. When it occurs, in most of the cases 1.5 associated to trumatized tissues or exposed wounds that are infested by the flies that deposit their og:g..s or larvaes. The clinical pictures depends on the location of the lessians, the number of eggs deposited„md the coup o flies capable of producing Mriasis. In our cases, the etiological agent was the Celfhli01711W fOn7ini•alav, i1.711.1C12 is included in the ne IV world SC/VW-WM-11M, distributed in North and South America. It is an obligatory parasit which feeds on lit ring tissue and can penetrate unbroken skin, but as explained belbre, also infests WOUI7C15. Our cases were treated using products very common in the practice of the tvterinary medicine, such as Ivermectine and Creoline, with excelent resaults and without important side effects in humans. The pharmacological treatment WaS complemented with the surgical elimination of the Dart rues. Ivermectine is a synthetic macracielic lactone„ and Crook-no is a ml wture of differents monovalent phenols. The present report corresponds to three new cases of oral myiasis treated succesfizIly using the methodology already mentioned, and R-hich were seen at the Lnit of Stomatolagy and Makillalati Surgery’ at the Universitary Hospital San Vicente de Paul in Medellin, Colombia, South America. It is important to emphasize the unusual location of the pathology, the succes of the therapy and the few reports published at the literature.